PATHOPHYSIOLOGY OF CENTRAL CEREBRAL EDEMA LITERATURE REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The brain is a tissue with high metabolic activity, for which this organ, accounting for only 2% of body weight, consumes 20% of all incoming oxygen and glucose [6,7]. Brain damage leads to disruption of oxygen and nutrient supply with the development of energy deficiency, accompanied by cerebral edema (CEE), a severe life-threatening condition that worsens the prognosis of the disease. From the mid-20th century to the present, classical methods of CEE correction have been used that do not have a serious evidence base, such as the introduction of mannitol or hypertonic saline, hyperventilation, and in critical cases, decompression craniotomy. The past 30 years have been marked by significant discoveries in the physiology and pathology of fluid exchange in the central nervous system (CNS), including that accompanied by water accumulation in the brain parenchyma [1,5,14,]. This may facilitate a revision of approaches to the treatment of central cerebral edema based on the molecular biology of water and electrolyte transport systems across brain barriers.